Low energy availability in a sleep-low training study - Mettler, S.; Muller, B.; Haudum, J. (Medicine & Science in Sports & Exercise, 2017)
Letter to the editor concerning Marquet LA, Brisswalter J, Louis J, et al. Enhanced endurance performance by periodization of carbohydrate intake: "sleep low" strategy. Med Sci Sports Exerc. 2016;48(4):663-72.